2021
DOI: 10.1007/s13278-021-00772-w
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-platform comparison of framed topics in Twitter and Weibo: machine learning approaches to social media text mining

Abstract: While the salience of social media platforms on modern interactive communication between diverse social actors has been demonstrated, less academic attention has been paid to comparisons between framed topics and user interactions across social media platforms, such as Twitter and Weibo. This article suggests text mining and natural language processing tools for cross-platform comparative social media studies, based on Latent Dirichlet Allocation (LDA) and social network analysis. This study illustrates how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 115 publications
0
8
0
1
Order By: Relevance
“…The two share many similarities, such as a large number of users, a huge amount of user-generated content, continuous and rapid growth, and the same content distribution model and core functions. The nature of social media data, which stores rich textual data about user interactions, can help us understand what users are thinking about a topic or event, enabling systematic analysis of the structure or patterns of activity among individuals or groups ( Yang et al, 2021 ). Research in psychology has also found strong support for the usefulness and validity of integrative language analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The two share many similarities, such as a large number of users, a huge amount of user-generated content, continuous and rapid growth, and the same content distribution model and core functions. The nature of social media data, which stores rich textual data about user interactions, can help us understand what users are thinking about a topic or event, enabling systematic analysis of the structure or patterns of activity among individuals or groups ( Yang et al, 2021 ). Research in psychology has also found strong support for the usefulness and validity of integrative language analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mediante este proceso, se han excluido comunidades cuyas descripciones son demasiado genéricas ("soy", "amo", "love" o "like"); o bien que responden únicamente a un criterio geográfico. Diferentes trabajos han señalado el valor de estas técnicas para caracterizar las comunidades de usuarios de las redes, así como para comparar las interacciones entre ellas (Yang et al, 2021).…”
Section: Metodologíaunclassified
“…Policies on employee social media usage tend to vary across organizations, sectors, and countries (Jacobson & Tufts, 2013). Most private sector organizations create their own social media policy or guidelines and are generally able to dismiss their workers from employment because of what an employee has written on social media posts (Schmidt & O’Connor, 2015; Yang et al, 2021). However, public sector social media policies are distinctive; some may require that a series of legislations be passed to implement social media-related workplace rules.…”
Section: Literature Reviewmentioning
confidence: 99%